Climate change adaptation and mitigation in agriculture: Science workshop report - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2010)
CGIAR and partner scientists met in Cancun, Mexico, with the purpose to advance science on climate change adaptation and mitigation, according to the scope of the CGIAR Research Program on Climate Change, Agriculture and Food security (CCAFS). The objectives of the workshop were to (1) understand ongoing research as a foundation for future collaboration and advances, and (2) explore research that shows the highest promise for scientific breakthroughs.